2008
DOI: 10.1007/s00264-008-0599-7
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder arthrodesis with a reconstruction plate

Abstract: From 1995 to 2005, arthrodesis with a reconstruction plate was performed for eight shoulders. The average follow-up period was 44 months. The indications for shoulder arthrodesis were joint destruction as a sequel of tuberculous arthritis, malignant bone tumour, pyogenic arthritis, failed arthrodesis and paralysis of the brachial plexus. The evaluation criteria included bony union and pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…16,25,37 With the use of perioperative antibiotics, Dimmen and Madsen 39 (series of 18) and Chun and Byeon 25 (series of 8) had no infections, while other studies previously have demonstrated 0% to 14% infection rates. 2,22,23,25,[39][40][41] In terms of postoperative fracture, up to 11% of patient's undergoing arthrodesis have had humeral Figure 5. A, Thirty-seven-year-old female laborer with history of prior trauma to right shoulder with recurrent instability associated with poor glenoid bone stock that persisted despite multiple instability procedures.…”
Section: Complicationsmentioning
confidence: 90%
See 1 more Smart Citation
“…16,25,37 With the use of perioperative antibiotics, Dimmen and Madsen 39 (series of 18) and Chun and Byeon 25 (series of 8) had no infections, while other studies previously have demonstrated 0% to 14% infection rates. 2,22,23,25,[39][40][41] In terms of postoperative fracture, up to 11% of patient's undergoing arthrodesis have had humeral Figure 5. A, Thirty-seven-year-old female laborer with history of prior trauma to right shoulder with recurrent instability associated with poor glenoid bone stock that persisted despite multiple instability procedures.…”
Section: Complicationsmentioning
confidence: 90%
“…9 Regardless of precisely measured positions, intraoperatively the shoulder should be positioned to optimize patient function and facilitate reaching the mouth, waist, back pocket, and contralateral shoulder ( Figure 2). 2,9,15,17,23,25,34 Although the literature defines the angles stated earlier, it is practically important for an individual patient, with a specific individual body habitus, to be able to achieve the expected activities of daily living, and the angles of fusion appropriately titrated.…”
Section: Ideal Fusion Positionmentioning
confidence: 99%
“…With this position the patient can comfortably reach his or her mouth, belt buckle, and contralateral shoulder. Shoulder arthrodesis with recostruction plates has merits in that the plate can be bent easily depending on the anatomical location, there is less skin stimulation since the internal fixation used has few protrusions and adequate bone arthrodesis can be achieved [47]. Therefore, arthrodesis with a reconstruction plate is recommended by many researches [46,48].…”
Section: Studymentioning
confidence: 99%
“…Radiologisch wurde die vollstän-dige knöcherne Konsolidierung nach durchschnittlich 4,0 (2,9) Monaten dokumentiert. Die knöcherne Durchbauung eines der beiden Arthrodeseflächen -des akromiohumeralen oder glenohumeralen Gelenks -wurde durchschnittlich nach 3,4 (1,(4)(5)9) …”
Section: Operationsprinzip Und -Zielunclassified